A 2-strain mixture of Lactobacillus acidophilus in the treatment of irritable bowel syndrome: A placebo-controlled randomized clinical trial. Issue 5 (May 2020) - Sadrin, Stéphane; Sennoune, Souad; Gout, Bernard; Marque, Sébastien; Moreau, Jacques; Zinoune, Karim; Grillasca, Joël-Paul; Pons, Olivier; Maixent, Jean-Michel
Abstract: Background: In the absence of a well-established therapeutic approach, patients with irritable bowel syndrome seek alternative strategies such as probiotics. Aims: The current trial named LAPIBSS aimed to demonstrate the efficacy of a 2-strain mixture of Lactobacillus acidophilus to improve irritable bowel syndrome symptoms. Methods: Eighty patients diagnosed for irritable bowel syndrome were recruited to a multicentre, double-blinded, in parallel groups, placebo-controlled, randomized clinical trial. Patients were provided with a daily dose of two capsules containing either probiotics (5 × 10 9 cfu/capsule) or placebo for 8 weeks. The primary outcome was abdominal pain score assessed with a 100-mm visual analogue scale. Secondary outcomes included scores of bloating, flatus and rumbling assessed with a 100-mm visual analogue scale, a composite score and bowel habits. Results: Abdominal pain score was significantly improved in both groups at weeks 4 and 8 ( P < 0.0001), but no significant differences were found between groups at week 8 (19.0 ± 2.5 vs 25.1 ± 2.6, respectively; LS Means differences = 6.0 ± 3.2; P = 0.06). Significant differences between groups were observed for flatus score at week 4 ( P = 0.04) and week 8 ( P = 0.03) and composite score ( P = 0.04) at week 8. Conclusions: The consumption of the 2-strain mixture of L. acidophilus over 8 weeks is safe and decreases significantly flatus and composite scores. Trial registration number: EudraCT No 2008 A00844-51.